2018
DOI: 10.1093/mnras/sty2986
|View full text |Cite
|
Sign up to set email alerts
|

On the post-common-envelope central star of the planetary nebula NGC 2346

Abstract: The common-envelope phase is one of the most poorly understood phases of (binary) stellar evolution, in spite of its importance in the formation of a wide-range of astrophysical phenomena ranging from cataclysmic variables to cosmologically important supernova type ia, and even recently discovered gravitational wave producing black hole mergers. The central star of the planetary nebula NGC 2346 has long been held as one of the longest period post-common-envelope systems known with a published period of approxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The companions' radii were derived using R2/R = (M2/M ) 0.8 (Torres et al 2010), which can be shown to be reasonably close to the measured values when such values exist, even accounting for the fact that post-CE companions tend to be larger than their mass would dictate due to irradiation by the primary (De Marco et al 2008), or by recent accretion during the CE phase (Jones et al 2015). In at least one case, V651 Mon, Brown et al (2019) strongly suspects that the secondary is on the subgiant branch and therefore quite a bit larger than our assumption. The final separation, a f , is that derived from the observed period, this could be somewhat smaller than the one after the CE event because of magnetic braking (Zorotovic et al 2011a), though not enough to shift the data points in our logarithmic plots.…”
Section: The Observational and Reconstructed Datamentioning
confidence: 63%
See 2 more Smart Citations
“…The companions' radii were derived using R2/R = (M2/M ) 0.8 (Torres et al 2010), which can be shown to be reasonably close to the measured values when such values exist, even accounting for the fact that post-CE companions tend to be larger than their mass would dictate due to irradiation by the primary (De Marco et al 2008), or by recent accretion during the CE phase (Jones et al 2015). In at least one case, V651 Mon, Brown et al (2019) strongly suspects that the secondary is on the subgiant branch and therefore quite a bit larger than our assumption. The final separation, a f , is that derived from the observed period, this could be somewhat smaller than the one after the CE event because of magnetic braking (Zorotovic et al 2011a), though not enough to shift the data points in our logarithmic plots.…”
Section: The Observational and Reconstructed Datamentioning
confidence: 63%
“…In addition, the nebula can be used to suggest, though not guarantee, that the giant was on the asymptotic giant branch (AGB) rather than on the red giant branch (RGB) at the time of the CE, something that is less certain for other binaries where Mc 0.47 M (see below). All the PN we use are those listed in De Marco et al (2011) with the addition of 10 objects: UU Sge and KV Vel, V664 Cas and A 65 (as listed by Davis et al 2010), HaTr7 andESO 330-9 (Hillwig et al 2017), M3-1 (Jones et al 2019), Hen 2-155 (Jones et al 2015), Sp 1 (Hillwig et al 2016b) and V651 Mon (as recently revised by Brown et al 2019, note that for this object the companion may not be a main sequence star but instead a subgiant, if so then the secondary would be much closer to filling its Roche radius than we have listed in Table A2). Finally, we include all the sdO and sdB objects listed by Davis et al (2010) and most of those listed by Schreiber & Gänsicke (2003), with the exclusion of MT Ser and V477 Lyr.…”
Section: The Observational and Reconstructed Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the right panel we show a comparison with the rotational periods of pulsating white dwarfs (light green with dashed contours, values taken from Kawaler 2004;Hermes et al 2017a) and apparently single magnetic white dwarfs (bold yellow lines, values taken from Ferrario et al 2015). We note that there are also a few longer period magnetic white dwarfs (Putney & Jordan 1995;Bergeron et al 1997;Schmidt et al 1999;Kawka & Vennes 2012) and PCE binary central stars (Miszalski et al 2018a,b;Brown et al 2019), which we omit from Fig. 8 for better visibility.…”
Section: Periodsmentioning
confidence: 96%
“…Models such as the Grazing Envelope Evolution proposed by Soker (2015) and Shiber et al (2017), in which the companion grazes the envelope of the RGB or AGB star while both the orbital separation and the giant radius shrink simultaneously over the course of tens to hundreds of years, could perhaps help explain the phenomenon. A model along these lines could, for instance, provide some insight in the case of NGC 2346, a particularly massive SD system with a relatively long post-CE orbital period in which the primary is believed to be a post-RGB star (Brown et al 2019). At any rate, CE interaction would probably need to last long enough to allow for a considerable amount of the primary's envelope mass to get diluted into the ISM beyond detectability, in order for the presumed envelope mass at the time of a later "full" CE ejection to be reconciled with the mass of the observed nebulae.…”
Section: Samplementioning
confidence: 99%